Konsep Islam tentang Keadilan: Kajian Interdisipliner - Taqiyuddin, Hafidz (Aqlania, 2019)
This article explores justice as conceptualized by Islam in various scholars. In Islam, in addition to obligations, there are also so-called rights. Related to these rights, of course, cannot be separated from what is called justice or a sense of fairness. Justice contained in Islamic teachings is doctrinated by various scientific aspects, be it philosophy, morals, theology or law. This research discusses specifically the relationship between rights and justice as conceptualized and taught in Islam. The result is that in Islam, the granting and provision of rights to a person or group cannot be separated from the existence of an important principle, namely justice.